The Veil Lifted: Inclusive Improvisation, Virtual Music Learning Environments, and the Pandemic that Unwittingly Pitted Academia Against Ableism - Argyropoulos, Erica K. (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
The COVID-19 pandemic has highlighted many disparities between diverse social and cultural groups, both inside the academy and throughout society at large. In this essay, Erica K. Argyropoulos reflects on her own experiences as a disabled, nonbinary person in academia during the COVID-19 pandemic.